2017
DOI: 10.1242/dev.149856
|View full text |Cite
|
Sign up to set email alerts
|

Essential basal cytonemes take up Hedgehog in the Drosophila wing imaginal disc

Abstract: Morphogen concentration gradients that extend across developmental fields form by dispersion from source cells. In the Drosophila wing disc, Hedgehog (Hh) produced by posterior compartment cells distributes in a concentration gradient to adjacent cells of the anterior compartment. We monitored Hh:GFP after pulsed expression, and analyzed the movement and colocalization of Hh, Patched (Ptc) and Smoothened (Smo) proteins tagged with GFP or mCherry and expressed at physiological levels from bacterial artificial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
174
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(185 citation statements)
references
References 56 publications
11
174
0
Order By: Relevance
“…1 and 2). This is consistent with previous studies that reported increased signaling between tumor and stromal cells in this model (Herranz et al, 2014), and with the presence of cytonemes in many other contexts of paracrine signaling (Bischoff et al, 2013;Chen et al, 2017;Eom et al, 2015;Inaba et al, 2015;Roy et al, 2014;Sanders et al, 2013;Stanganello et al, 2015). We confirmed that Dpp is expressed by the tumor cells ( Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…1 and 2). This is consistent with previous studies that reported increased signaling between tumor and stromal cells in this model (Herranz et al, 2014), and with the presence of cytonemes in many other contexts of paracrine signaling (Bischoff et al, 2013;Chen et al, 2017;Eom et al, 2015;Inaba et al, 2015;Roy et al, 2014;Sanders et al, 2013;Stanganello et al, 2015). We confirmed that Dpp is expressed by the tumor cells ( Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Downregulation of diaphanous (dia), Neuroglian (Nrg), SCAR or Capricious (Caps) reduces the number and length of cytonemes, and reduces signaling in tracheal cells, myoblasts and wing disc cells (Bischoff et al, 2013;Huang and Kornberg, 2015;Roy et al, 2014). We expressed RNAi constructs to lower Dia, Nrg, SCAR and Caps levels in tumor cells, using conditions that represent partial loss-of-function and do not perturb cell polarity, cell viability, or cell cycle during normal development (Chen et al, 2017;Kornberg, 2015, 2016;Roy et al, 2014). We monitored wing discs for morphology, Cut expression, and pMAD.…”
Section: Genetic Suppression Of Tumor Phenotypesmentioning
confidence: 99%
“…n-Syb is functionally interchangeable with the other (Syb) (48), which is expressed ubiquitously and has a general role in membrane trafficking (Chin et al, 1993). In the wing pouch primordium of the wing disc, Syb is required for Wingless signaling (49) and by the cytonemes of the Hh-producing cells of the wing disc (8). Wing disc expression of the sybRNAi used by Yamazaki et al (49) stunted ASP growth and reduced Dpp signal transduction, and reduced the number of ASP cytonemes (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the ASP, cytoneme-mediated signaling has been implicated in Drosophila tissues such as the wing disc epithelium (48), abdominal histoblasts (6), testis (9), and the hematopoietic stem cell niche (10), and in zebrafish embryos (1113), chick embryos (14), mouse embryos (15), and cultured cell systems (16). In signal producing cells, cytoneme-mediated signaling is dependent on the signaling proteins and requires proteins that process and prepare the signaling proteins for release (17).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies used CherryCAAX, CD8:Cherry, CD4:IFP2, CD2:GFP, and CD8:GFP to image cytonemes from larval tissues [21,23,24, 39,41]. We successfully imaged the embryonic cytonemes using all these constructs.…”
Section: Notesmentioning
confidence: 99%